2004
DOI: 10.1124/jpet.104.070300
|View full text |Cite
|
Sign up to set email alerts
|

The Role of 5-Hydroxytryptamine3 Receptors in the Vagal Afferent Activation-Induced Inhibition of the First Cervical Dorsal Horn Spinal Neurons Projected from Tooth Pulp in the Rat

Abstract: To test the hypothesis that vagal afferent (VA) stimulation modulates the first cervical dorsal horn (C 1 ) neuron activity, which is projected by tooth pulp (TP) afferent inputs through the activation of a local GABAergic mechanism via 5-hydroxytryptamine 3 (5-HT 3 ) receptors, we used the technique of microiontophoretic application of drugs. In pentobarbitalanesthetized rats, we recorded C 1 spinal neuron activity responding to TP stimulation. The TP stimulation-evoked C 1 spinal neuron excitation was inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The activation of 5-HT 3 and 5-HT 7 receptors on inhibitory neurons by nVNS would enhance the descending inhibitory pain pathway via activation of spinal interneurons and release of the inhibitory neurotransmitters, GABA and glycine, to suppress ascending pain transmission. This mechanism is supported by other orofacial pain studies involving trigeminal nerve activation in which direct stimulation of the vagus nerve was shown to exhibit anti-nociceptive effects, to facilitate the serotonergic descending inhibition pathway, and to modulate inhibition of GABAergic neurons (14,40,41). Other mechanisms may also be involved in nVNS inhibition of trigeminal pain signaling.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The activation of 5-HT 3 and 5-HT 7 receptors on inhibitory neurons by nVNS would enhance the descending inhibitory pain pathway via activation of spinal interneurons and release of the inhibitory neurotransmitters, GABA and glycine, to suppress ascending pain transmission. This mechanism is supported by other orofacial pain studies involving trigeminal nerve activation in which direct stimulation of the vagus nerve was shown to exhibit anti-nociceptive effects, to facilitate the serotonergic descending inhibition pathway, and to modulate inhibition of GABAergic neurons (14,40,41). Other mechanisms may also be involved in nVNS inhibition of trigeminal pain signaling.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast, the inhibitory effect of nVNS as an acute migraine treatment is proposed to promote multiple distinct cellular changes and pathways within the brain and spinal cord to facilitate descending pain modulation (13). The descending inhibitory pathway is known to involve activation of 5-HT3 and 5-HT7 receptors on inhibitory interneurons that stimulates release of glycine and GABA, which act as inhibitory neurotransmitters of primary or secondary trigeminal nociceptors (14). Thus, the reported efficacy of nVNS may involve modulation of GABAergic and serotonergic signaling but this pathway has not been demonstrated in episodic migraine models.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that anesthetics enhance GABA A receptor mediated synaptic currents, thus increasing the inhibitory drive in neuronal networks. However, it has to be remembered that 5-HT 3 receptors are located on some inhibitory GABAergic interneurons in the amygdala (Koyama et al, 2000), cortex (Zhou and Hablitz, 1999;Puig et al, 2004), hippocampus (McMahon and Kauer, 1997), and spinal cord (Alhaider et al, 1991;Tanimoto et al, 2004) and can control the release of GABA into the synapse, presumably through Ca 2ϩ -permeable homomeric 5-HT 3A receptors (Koyama et al, 2000). Hence, anesthetic modulation of 5-HT 3 receptors in these areas will affect GABA release and change the in- Recently, a study showed that 5-HT 3 receptor antagonists reduce the halothane-mediated inhibition of spinal dorsal horn sensory neuronal responses to noxious peripheral stimulation, indicating that 5-HT 3 receptors are anesthetic targets for the reduction in nociception (Koshizaki et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The technique of iontophoretic application was the same as described in our previous reports. 17,18,25,31 One of the two lateral barrels of the micropipette contained 160 mmol/L NaCl which was used for balancing currents to prevent the occurrence of tip polarization artifacts. The remaining lateral barrel contained NMDA (200 mmol/L in 160 mmol/L NaCl, pH 8.5) or L-glutamate (100 mmol/L in 160 mmol/L NaCl, pH 8.5; Nacalai Tesque, Kyoto, Japan), as described previously.…”
Section: Methodsmentioning
confidence: 99%